Informational externalities of seasoned equity issues - Slovin, Myron B.; Sushka, Marie E.; Polonchek, John A. (Journal of Financial Economics, 1992)
We examine share-price reactions of commercial bank common stock issues and find negative effects on rival commercial and investment banking firms. In comparison, we find no such intra-industry effects for equity issues by industrial firms. Our results support theoretical models in which bank loan portfolios impound asymmetric information about client firms, so that adverse individual bank announcements generate external information effects on other banks. A policy implication of these results is that regulatory pressures applied to individual banks induce spillover costs for the commercial and investment banking industries. Our evidence also indicates that the legal separation of commercial and investment banking activities is artificial.